(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Triple-negative breast cancer is a type of cancer that has absence in certain receptor systems like Human epidermal growth factor receptor-2 (HER2), progesterone receptor (PR), and oestrogen receptor (ER) (1). It is tough to treat, and there aren't many therapies that work right now. Through the use of nanoparticles, researchers have developed new approaches to treat patients with TNBC. These new drugs are designed to target the different genetic mutations that are known to affect the development of this disease. The use of NDDSs with nano herbal technology has numerous advantages, such as their ability to improve the therapeutic outcome, and systemic action and reduced systemic toxicity.